2014
DOI: 10.1371/journal.pone.0095645
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide Resistance, Mycobacterium tuberculosis Lineage and Treatment Outcomes in San Francisco, California

Abstract: BackgroundPyrazinamide (PZA) is a first line agent for the treatment of active tuberculosis. PZA is also considered a potent companion drug for newer regimens under development. There are limited data on the demographic, clinical, and pathogen characteristics of PZA resistant tuberculosis.MethodsUsing a retrospective cohort study design, we evaluated all PZA resistant M. tuberculosis (M.tb) and M. bovis cases reported in San Francisco from 1991 to 2011. Demographic, clinical, and molecular data were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…Except for three cases (two of which were caused by PZA r isolates), all smear and culture conversions occurred within 6 months of treatment. These data reveal that the treatment outcome may not be heavily influenced by the PZA susceptibility status, which has also been described by earlier researchers ( 37 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Except for three cases (two of which were caused by PZA r isolates), all smear and culture conversions occurred within 6 months of treatment. These data reveal that the treatment outcome may not be heavily influenced by the PZA susceptibility status, which has also been described by earlier researchers ( 37 ).…”
Section: Discussionsupporting
confidence: 88%
“…Due to an insufficient sample size, we were unable to conclude that PZA susceptibility does not significantly associate with the genetic type of the M. tuberculosis isolates. However, a study from California also showed that PZA susceptibility does not correlate with the genetic lineage of M. tuberculosis ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference (P > 0.05) was observed between the PZA-monoresistant and PZAsensitive patients in total and partial lesion elimination rates after the intensive phase ( Table 3). This is consistent with our previous study [23] and a recent report in San Francisco, California [24]. Liang et al reported that the multiple drug resistance, but not the single drug-resistance, could alter the sputum conversion after 2 months treatment [25].…”
Section: Discussionsupporting
confidence: 93%
“…; Budzik et al . ). Multiplex PCR targeting to the RD1 gene has been validated for dual detection of MTC and Myco.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the naturally pyrazinamide (PZA) resistant Myco. bovis (Konno et al 1967) and PZA-monoresistant M. tuberculosis should be considerably identified (Kurbatova et al 2013;Budzik et al 2014). Multiplex PCR targeting to the RD1 gene has been validated for dual detection of MTC and Myco.…”
Section: Ifmentioning
confidence: 99%